Identity erosion in Bret Easton Ellis' Less Than Zero and Imperial Bedrooms. - Kalimani, Sara Vahabi (2014)
The present study concerns itself with identity erosion in Ellis’ two novels, Less Than Zero (1985) and Imperial Bedrooms (2010), the latter of which is the sequel to the former. The focus of research is to explore two objectives by applying postmodern theory. Firstly, the characters were studied in terms of their portrayal of postmodern features and the novels were investigated in terms of narration and the features that have been categorised as postmodern and postmodernist fiction. Secondly, the next objective was to explore the protagonist’s identity erosion through 25 years, from Less Than Zero, when he was teen aged, to Imperial Bedrooms, when he is an adult and a business person. Although Ellis is more famous for his novel American Psycho, these two mentioned novels were selected because a sequel provides an opportunity to explore the character’s identity erosion precisely and observe the changes he went through. The other reason for this preference was that these novels are cultural satires of contemporary society. Therefore, this study specifically analysed the postmodern identity presented in Ellis’ novels. Through this study, theories of postmodern theorists such as Baudrillard (1983), Kellner (1992), and Jameson (1991) were used to support the argumentation. Baudrillard’s (1983) simulation supported the argumentation concerning postmodern conspicuous consumption, and Kellner (1992)’s ideas of identity erosion supported the changes postmodern identity is experiencing today. Finally, Jameson’s (1991) concept of postmodern narrative supported argumentation concerning Ellis’ narrative style. The selected methodology for this study was qualitative with employing textual analysis of the characterization in both novels. In this regard, the major characters of both novels were explored in terms of their behaviour. Since simulation and commodification are the two prominent features of postmodernity, this study focused on how these features appear in Ellis’ novels and give the characters face values and new identities, as well. This is done by examining characters’ symbolic interactions in terms of objects they used and behaviour they show in different social contexts.